Penerapan Extreme Programming Pada Sistem Informasi Pembayaran Sumbangan Pembinaan Pendidikan (SPP) - Arief Rusman; Siti Lutfiyah Angraini (LPPM Universitas Bina Sarana Informatika, 2019)
The use of information and communication technology is one of the technological developments that can provide benefits in the field of education such as in the management of school payments. The school payment process requires fast and accurate data processing in terms of payment and storage until report generation. The purpose of this research is to make a school payment information system that is fast and accurate in its processing. With extreme programming method is expected to help resolve existing problems. The expected results will be an information system that can help the payment process in the school that is able to process payment data quickly and accurately to produce a payment data that can be used as a guideline for decision making by the school head masters. The expected form of report can also be more easily understood than before using an information system. In the process of storing data it is also expected to be better because it does not use paper but can already be stored in a database system that is connected to an information system